2021
DOI: 10.1002/ehf2.13558
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular dysfunction and tricuspid regurgitation in functional mitral regurgitation

Abstract: Aim The objective of this study was to investigate the prognostic importance of right ventricular dysfunction (RVD) and tricuspid regurgitation (TR) in patients with moderate–severe functional mitral regurgitation (FMR) receiving MitraClip procedure. RVD and TR grade are associated with cardiovascular mortality in the general population and other cardiovascular diseases. However, there are limited data from observational studies on the prognostic significance of RVD and TR in FMR receiving MitraClip procedure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…RV-PA coupling assesses RV systolic performance according to the afterload and its prognostic utility in various HF and valvular heart disease populations have been demonstrated. 49) 50) 51) 52) Thus far, 2 studies have demonstrated the negative prognostic impact of abnormal RV-PA coupling on patients with FMR who underwent TEER. From the EuroSMR registry, 817 patients with FMR who underwent TEER were evaluated according to RV-PA coupling assessed by tricuspid annular plane systolic excursion-to-systolic pulmonary artery pressure (TAPSE/sPAP) ratio.…”
Section: Teer For Fmrmentioning
confidence: 99%
“…RV-PA coupling assesses RV systolic performance according to the afterload and its prognostic utility in various HF and valvular heart disease populations have been demonstrated. 49) 50) 51) 52) Thus far, 2 studies have demonstrated the negative prognostic impact of abnormal RV-PA coupling on patients with FMR who underwent TEER. From the EuroSMR registry, 817 patients with FMR who underwent TEER were evaluated according to RV-PA coupling assessed by tricuspid annular plane systolic excursion-to-systolic pulmonary artery pressure (TAPSE/sPAP) ratio.…”
Section: Teer For Fmrmentioning
confidence: 99%